Imported measles outbreak in a university. - Narain, J P (1985)
In 1981, a measles outbreak in an Arkansas university involved 16 students and four persons who were contacts of these students. The first two cases were in students who recently returned from Honduras. Of the 16 students with measles, 12 had significant gastrointestinal symptoms; five had elevated liver transaminase, and eight were hospitalized. Only two of the students were considered adequately immunized. A voluntary immunization clinic held on the university campus resulted in 67 per cent of 3,076 students being vaccinated.